Evaluation of lipid and mineral alterations in hypothyroid patients: A hospital-based case-control study - Poorana Priya. P (Journal of Neonatal Surgery, 2025)
Introduction: Hypothyroidism, a prevalent endocrine disorder, is known to adversely affect various metabolic pathways, particularly lipid and mineral metabolism. Alterations in thyroid hormone levels influence hepatic lipid regulation and mineral homeostasis, potentially increasing cardiovascular risk and contributing to systemic symptoms such as fatigue and muscle weakness. Despite this, routine screening for lipid and mineral abnormalities in hypothyroid patients is often overlooked in clinical practice, especially in resource-limited settings. Materials and Methods: A hospital-based prospective case-control study was conducted at a tertiary care center in Tamil Nadu, India, including 100 participants—50 newly diagnosed hypothyroid patients and 50 age- and gender-matched euthyroid controls. Serum thyroid hormones (TSH, FT3, FT4), lipid profile, and mineral levels (calcium, magnesium, phosphorus) were assessed using standard biochemical methods. Statistical analysis was performed using SPSS version 26.0, with independent t-tests and Pearson’s correlation. A p-value < 0.05 was considered statistically significant. Results: The mean age of the case group was 55.8 ± 14.9 years, slightly higher than controls (51.2 ± 15.6), but not statistically significant. Females predominated in both groups. FT3 and FT4 levels were significantly reduced (p < 0.05 and < 0.001, respectively), while TSH was markedly elevated (p < 0.001) in hypothyroid patients compared to controls. Serum calcium levels were significantly lower in the hypothyroid group (8.62 ± 0.69 mg/dL vs. 9.57 ± 0.62 mg/dL, p < 0.001). Magnesium and phosphorus levels were slightly elevated in hypothyroid patients, but the differences were not statistically significant (p > 0.05). Conclusion: Hypothyroidism is associated with significant alterations in thyroid hormones and calcium metabolism, with mild, non-significant changes in magnesium and phosphorus levels. These biochemical disturbances highlight the need for routine monitoring of lipid and mineral parameters in hypothyroid patients to ensure timely diagnosis and management of potential complications.